Peran kampus dan mahasiswa dalam meningkatkan peran serta masyarakat dalam pengelolaan sampah kota - Sasono, Bagus Arifianto (Waste Handling and Environmental Monitoring, 2024)
Waste management has become a critical priority in Indonesia to address the increasing volume of waste generated annually. Despite setting a 100% waste management target, achieving it is not easy due to challenges posed by human activities and population growth. The main issue faced is the lack of public awareness of their role in waste management. Campuses and academics from around the world are actively involved in developing sustainable waste management, including in Indonesia. Through programs and initiatives, campuses and students are expected to enhance community participation in waste management, creating strategies tailored to the Indonesian context. Literature review was utilized to summarize the role of campuses and students in waste management and its potential development. Data retrieval method involved secondary data search from various sources. Various strategies are proposed, including the development of specific programs, continuous education and monitoring, and identification of funding sources. Case studies from various campuses in Indonesia provide real insights into their efforts to improve waste management. The conclusion of this research emphasizes the importance of the role of campuses and students in raising awareness and actions of the community regarding waste management. Suggestions are made to strengthen the role of campuses and students, including the establishment of obligations, awareness of their role beyond the campus, development of effective strategies, and evaluation of the real impacts achieved.